2020
DOI: 10.3390/bs10040077
|View full text |Cite
|
Sign up to set email alerts
|

Personal Values Associated with Prosocial Decisions

Abstract: Social situations require people to make complex decisions, sometimes involving different outcomes for the self and others. Considering the long-lasting interest scholars are showing in the topic of social decisions, the aim of the current article is to add to this research line by looking at personal values as possible factors associated with a preference for more self-maximizing or cooperative choices. In a general adult sample (N = 63), we used the Social Value Orientation (SVO) slider measure to investigat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
17
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 19 publications
(17 citation statements)
references
References 34 publications
0
17
0
Order By: Relevance
“…Interestingly, the differences found during the study in respondents of different sexes did not coincide with data from other studies. Female participants had higher estimates of conservative values than male participants in the Renata M. Heilman and Petko Kusev study [6]. Men had a higher orientation to hedonism and stimulation than women in the Irem Metin-Orta and Kursad Demirutku study [19].…”
Section: Discussionmentioning
confidence: 86%
See 1 more Smart Citation
“…Interestingly, the differences found during the study in respondents of different sexes did not coincide with data from other studies. Female participants had higher estimates of conservative values than male participants in the Renata M. Heilman and Petko Kusev study [6]. Men had a higher orientation to hedonism and stimulation than women in the Irem Metin-Orta and Kursad Demirutku study [19].…”
Section: Discussionmentioning
confidence: 86%
“…Often, these studies consider the gender factor. Some researchers were able to establish the effect of gender on the structure of value orientations [5,6], while others did not [2]. Little attention is paid to the joint influence of age and gender factors on human values.…”
Section: Introductionmentioning
confidence: 99%
“…Our results showed that the prosociality of men and women became indistinguishable somewhat after the age of 25. The conflicting findings that have been reported with respect to gender differences can partially be attributed to the sampled populations, so that studies relying on younger respondents' pools, such as children, adolescents, or undergraduate students (e.g., [11,47,48]), tended to find a gender difference in prosocial behavior, while studies with older respondents groups did not (e.g., [13,15,49]). Researchers interested in gender differences should therefore be cautious selecting and interpreting their results with respect to the age of the sampled population.…”
Section: Discussionmentioning
confidence: 96%
“…It has to be noted that there is also one more study using the SVO slider measure, which reports no age effects [49]. However, it has to be acknowledged that their sample of 63 adults was relatively small and narrow with respect to age (the reported mean age was 31.92 with a standard deviation of 1.01 years) and therefore somewhat less informative for the age-related development of prosociality.…”
Section: Data Availability Statementmentioning
confidence: 97%
“…This result raised the possibility that an individual's discount rates are not stable, but instead, they might be highly dependent on various factors pertaining to the decisional context. In fact, recent research in other decisional situations, such as risk-taking [29,[47][48][49][50][51][52] or framing effects [53][54][55], has provided ample empirical support to the idea that decision preferences might be constructed and are highly sensitive to task-related and individual factors [56][57][58]. When it comes to framing effects, which refers to people's tendency to change their risk preferences when decisional alternatives are presented in gain or loss terms, studies have shown that people are more prone to framing effects in their decisions related to human life than in situations where decisions refer to animals [53,[59][60][61], money or properties [62,63], precious metal or artwork [64][65][66] or even aliens [67].…”
Section: Discussionmentioning
confidence: 99%